ANALISIS KEBIJAKAN PERUSAHAAN MELAKUKAN REVALUASI ASET TETAP: Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Tjahjono, Achmad; Sari, Ratna Haninditya (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2021)
Fixed asset recognition is one of the main problems in fixed asset accounting. The use of cost does not reflect the true value of the asset so that the asset value is irrelevant. The IFRS convergence PSAK allows the use of the fair value (revaluation method) of fixed assets to reflect the current price so that the asset value becomes higher. Thus financial reports will provide more relevant information to users of financial statements to be used as a basis for decision making. This study aims to determine the effect of leverage, liquidity, company size, decrease in operating cash flow, fixed asset intensity, company growth on company policies to revaluate fixed assets in banking companies listed on the Indonesia Stock Exchange in 2015-2019. The populations of this study was taken using purposive sampling method with a total of 42 companies. The data used are secondary data in the form of annual financial reports and analyzed using logistic regression analysis techniques with a significance level of 5%. The results of this study are leverage, liquidity, and a partial decrease in operating cash flow have a positive and insignificant effect on fixed asset revaluation. Company size, fixed asset intensity, and company growth partially have a positive and significant effect on fixed asset revaluation. Taken together, the variables have a significant effect and are able to explain the variability to the dependent variable by 33,4%.